Study on the Propagation Law of Water Hammer Wave in Underwater Blasting and the Reducing Effect of Air Curtain on Water Hammer Wave - Chao Qi; Zuxiang Hu; Suihong Wang; Zhixiong Jiang; Haoyuan Wu; Zhiqiang Yin (Shock and Vibration)
The harmful effects (water hammer wave, flying stone, and broken quality of concrete) produced in the process of underwater drilling and blasting are the key factors affecting the safety of underwater drilling and blasting. In fact, the harm caused by the water hammer wave is the most significant. As a consequence, it is of great significance to study the propagation law of water hammer waves. Based on the background of the cofferdam demolition project at the inlet section of Shibishan Central Canal in Ningguo City, China, a three-dimensional numerical model was established based on Coupled Eulerian–Lagrangian (CEL) method. Besides, the propagation law of water hammer waves at different water depths with different millisecond times was studied. Meanwhile, the reduction effect of the water hammer wave at different positions of the bubble curtain was analyzed. The results showed that, in the direction of the minimum resistance line of the charge, the attenuation law of the water hammer wave is accorded with the Cole formula and attenuated exponentially. The attenuation speed of the water hammer wave increased at first and then decreased with the increase of the millisecond time. In addition, the attenuation rate of the peak pressure was the fastest when the millisecond interval 30 ms was used. The attenuation of the water hammer wave at different water depths decreased at first and then decreased with the increase of water depth. The attenuation law of the water hammer wave decreased linearly with the increase of the distance between the bubble curtain and the charge. The research results can provide particular guiding significance for similar on-site construction.